Strengthening Clean and Healthy Living Behavior (PHBS) for Elementary School Children in Gowa Regency - Bunga, Elfira Indri; Bahri, Nadya Tri Wulandari; Kusumawardani, Diva Fadliah; Baddulu, Nia Aulyah; Junadi, Nur Afifah; Nurazizah, Izdihar; Irmayanti, Irmayanti; Nasrah, Nasrah; Rachmat, Muhammad (Yayasan Mestika Nusantara Satu, 2024)
School age children (6-12 years old) are very vulnerable to health problems. Therefore, awareness of the importance of health needs including personal hygiene to be instilled from an early age, one of which is through programs to strengthen clean and healthy living behavior (PHBS). This community empowerment aims to improve the knowledge, attitude, and behaviors of clean and healthy living behavior (PHBS) in elementary school students grade 4, 5 and 6. Community empowerment was performed in eight elementary schools spread across four villages in Pattallassang sub-district, Gowa Regency, namely Je'nemadinging Village, Pacellekang Village, Panaikang Village, and Pakatto Village which included 272 students. The community empowerment model was implemented through lectures, educational games and practice. Educational materials include Handwashing with Soap (CTPS), Stop Open Defecation, and healthy snacks. The results of the community empowerment were evaluated using pretest and posttest questionnaires distributed to participants before and after the education. Questions on the questionnaire include questions to measure participants' knowledge, attitudes, and behaviors. The result of these activities was an increase in the knowledge, attitudes, and behavior regarding PHBS in most of the elementary school students from the four villages that became the location of the community empowerment.